Adsorption Behavior of Sr(II) from High-level Liquid Waste using Crown Ether with Ionic Liquid Impregnated Silica Adsorbent. (December 2017) - Kudo, Tatsuya; Ito, Tatsuya; Kim, Seong-Yun
Abstract: 4'4'(5')-di( tert -butylcyclohexano)-18-crown-6 (DtBuCH18C6) modified with 1-ethyl-3-methylimidazolium bis (trifluoro methylsulfonyl) imide ([C2 mim][NTf2 ]) was loaded onto porous silica/polymer composite support (SiO2 -P) particles with a mean diameter of 50 μm and used to extract Sr(II) from HNO3 solutions. The effect of HNO3 concentration on the equilibrium kinetics and thermodynamic properties of Sr(II) uptake were investigated by batch methods. The adsorbent exhibited excellent adsorption selectively for Sr(II) over a wide range of HNO3 concentrations. The adsorption of Sr(II) in the presence of 3 M HNO3 on (DtBuCH18C6+[C2 mim][NTf2 ])/SiO2 -P attained equilibrium within 1 h, and a relatively large distribution coefficient ( K d ) of ca. 30 cm 3 ·g −1 was obtained. Kinetic data were successfully modeled using pseudo-second-order kinetics. The adsorption of Sr(II) was a spontaneous and exothermic process. The uptake isotherm of Sr(II) for (DtBuCH18C6+[C2 mim][NTf2 ])/SiO2 -P followed a Langmuir-type adsorption equation.